Fabricating polyacrylamide microbeads by inverse emulsification to mimic the size and elasticity of living cells. (9th December 2016) - Labriola, Nicholas R.; Mathiowitz, Edith; Darling, Eric M.
Abstract : Inverse emulsification was used to fabricate polyacrylamide (PAAm) microbeads with size and elastic properties similar to typical, mammalian cells. Abstract : Inverse emulsification was used to fabricate polyacrylamide (PAAm) microbeads with size and elastic properties similar to typical, mammalian cells. These biomimicking microbeads could be fluorescently stained and functionalized with a collagen type-I coating, post-polymerization, for tracking bead locations and promoting cell recognition/binding, respectively. By occupying a previously unfilled range of sizes and mechanical properties, these microbeads may find unique use in both biomedical and materials applications.